Si3N4 etch rates at various ion-incidence angles in high-density CF4, CHF3, and C2F6 plasmas - Kim, Jun Hyun; Kim, Chang Koo (Korean Journal of Chemical Engineering, 2020)
The behavior of Si3N4 etching with ion-incidence angle in high-density CF4, CHF3, and C2F6 plasmas was investigated to understand the effect of discharge chemistry on the etch characteristics of Si3N4. The normalized etch yield (NEY) plots suggest that for all plasmas considered herein, physical sputtering is more prevalent than ion-assisted chemical etching as the Si3N4 etching mechanism. In the cases of the CF4 and C2F6 plasmas, the NEYs at an ion-incidence angle of 60° were greater than unity because the thickness and the fluorine-to-carbon (F/C) ratio of the steady-state fluorocarbon films (st-st FC films) on the Si3N4 surfaces decreased and increased, respectively, as the ion-incidence angle was increased from 0° to 60°. In contrast, the NEY at this angle in the CHF3 plasma was close to unity, as a result of a small change (or a very marginal decrease) in the thickness and the F/C ratio of the st-st FC film. Additionally, the NEY at an ion-incidence angle of 60° was higher in C2F6 plasma compared to CF4 plasma because the changes in the thickness and the F/C ratio of the st-st FC film were greater in the C2F6 plasma than those in the CF4 plasma.
Keywords: Etching Mechanism; Ion-incidence Angle; Si3N4 Etching; Steady-state Fluorocarbon Film